Evaluation of resistance modulation in MDR Pseudomonas aeruginosa and Klebsiella pneumoniae using peppermint oil nanoemulsion: integrating antibacterial assays and molecular modeling - Ali, Sardar; Hussain, Firasat; Nousheen, Tehmeena; Rahim, Kashif; Majeed, Hamid; Niaz, Kamal; Khan, Muhammad Nadeem (Frontiers in Microbiology, 2025)
IntroductionMultidrug-resistant urinary tract pathogens, primarily Klebsiella pneumoniae and Pseudomonas aeruginosa, represent a significant and growing public health challenge. The overuse of antibiotics has accelerated the development of resistance, creating an urgent need for alternative antimicrobial strategies. This study aimed to evaluate the antibacterial efficacy of a peppermint oil nanoemulsion (PEONE) against clinical multidrug-resistant (MDR) isolates of K. pneumoniae and P. aeruginosa, with a specific focus on its potential for resistance modulation and its mechanism of action.MethodsClinical isolates were obtained from patients with urinary tract infections and their antibiotic susceptibility profiles were determined. The PEONE was prepared using ultrasonic emulsification and characterized, revealing a droplet size of 190.21 ± 0.5 nm and a polydispersity index (PDI) of 0.15 ± 0.021. Antibacterial activity was assessed by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Membrane integrity was evaluated using DNA and protein leakage assays, and bacterial killing over time was measured with time-kill kinetics. Furthermore, molecular docking and 100 ns molecular dynamic simulations were performed against β-lactamase enzymes (PDB: 4EXY from K. pneumoniae, 6R73 from P. aeruginosa) to identify key bioactive components within the nanoemulsion.ResultsThe bacterial isolates were resistant to Levofloxacin, Penicillin G, Ceftazidime, and amoxicillin-clavulanic acid (AMC). PEONE demonstrated potent antibacterial activity, with an MIC of 0.1% v/v and an MBC of 0.14% v/v. DNA and protein leakage increased significantly (p < 0.05) with higher PEONE concentrations, indicating bacterial membrane disruption. Time-kill assays showed a sustained reduction in bacterial viability over 72 hours, with significant differences emerging after 12 hours of exposure. Molecular docking revealed that caryophyllene, a major component of peppermint oil, had the highest binding affinity against both β-lactamase targets (−9.2 kcal/mol for 4EXY; −7.1 kcal/mol for 6R73). The stability of this binding was confirmed through molecular dynamics simulations.DiscussionThe findings indicate that PEONE is effective at inhibiting and killing MDR K. pneumoniae and P. aeruginosa. The observed leakage of DNA and proteins suggests that the mechanism of action likely involves disruption of the bacterial membrane, leading to the loss of intracellular contents. This is further supported by the computational data, which identified caryophyllene as a key component with stable binding to resistance-associated β-lactamase enzymes. These results position PEONE as a promising, plant-based alternative for combating antibiotic-resistant urinary tract infections. Further in vivo studies are warranted to explore its clinical applicability and safety profile.